THE URGENCY OF CRITICAL THINKING DISPOSITION IN MATHEMATICS LEARNING IN THE INDEPENDENT CURRICULUM - Silwana, Amalia; Widayanti, Evi (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
The purpose of this article is to describe the definition and characteristics of critical thinking disposition, mathematics learning in the independent curriculum, and to analyze the urgency of critical thinking disposition in mathematics learning, especially in the application of mathematics learning in the independent curriculum. This research is descriptive research using the systematic literature review method through searching for accurate and relevant references, namely articles, books, and other relevant sources. From the results of the analysis, it is concluded that the urgency of critical thinking disposition in mathematics learning in the independent curriculum can be seen from several dimensions of the Pancasila student profile, especially the critical reasoning dimension which involves critical thinking disposition and needs to be built optimally and balanced in mathematics learning; the things that are emphasized in mathematics learning in the independent curriculum and involve critical thinking disposition include mathematical problem solving activities, student independence in understanding the mathematics material, and discussion and collaboration activities; mathematics learning models in the independent curriculum that direct students to involve critical thinking disposition; and projects to strengthen the Pancasila student profile in mathematics learning which involve critical thinking disposition in activities and their assessments